KOMUNIKASI INTERPERSONAL PENGEMUDI TAKSI ONLINE - Novia Amirah Azmi; Ernita Arif; Sarmiati Sarmiati (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
The presence of online taxis in the city of Padang is a source of new livelihood for the community. Hundreds of people from various backgrounds registered as Go-Car and GrabCar partners. In the beginning everything went smoothly. Problems began to emerge when the company raised the standard points and lowered the daily bonus amount. Partners who feel incompatible with these changes choose to resign while others are forced to survive in two ways, improve service or choose cheating in order to keep getting bonuses in the midst of difficulty reaching points. This study aims to describe the interpersonal communication activities between online taxi drivers and passengers and analyze communication efforts by the driver in providing services to passengers. This type of descriptive qualitative research with constructivist paradigms and phenomenological approaches. Informants are several active Go-Car and Grab-Car drivers in Padang City who have been operating for at least one year and randomly selected passengers. Data collection techniques in the form of in-depth interviews, involved observation and documentation. Data were analyzed based on phenomenological analysis by Edmund Husserl. Data validation uses data triangulation. The results showed that interpersonal communication activities can be seen from five positive attitudes namely openness, empathy, supportiveness, positive attitude and equality. The success of interpersonal communication can be seen through three indicators, success from the point of communicator, communicant and message.